PERSPEKTIF SOSIOLOGI TERHADAP PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DALAM PROSES PEMBELAJARAN DI PERGURUAN TINGGI - Lase, Apriliana; Sembiring, Feriel Amelia; Buulolo, Marlius; Simbolon, Nova Elisah (FISIP Universitas Malikussaleh, 2025)
This study aims to examine the use of Artificial Intelligence (AI) in universities that are rampant, especially in technology universities, studied from a sociological perspective. This type of research is qualitative descriptive sociological analysis. Data collection is used by means of observation, in-depth interviews and documentation techniques. The results of this study explain the use of technology in shaping interactions between lecturers and students in the learning process. This study focuses on how AI affects the Tridharma process of higher education, especially in the learning process in universities in technology universities. how AI interacts with the values and social norms that apply in the campus environment, as well as the use of AI in building and strengthening existing social interactions. The purpose of using artificial intelligence is to facilitate the learning process. There were no problems found regarding the limitations of interaction on campus, but the interaction between lecturers and students became closer due to this application.